Movimento estudantil e ditadura civil-militar em Santa Maria (1964-1968) - Lima, Mateus da Fonseca Capssa (2013)
This study investigates the action and organization of the Student Movement in Santa Maria, between 1964 and 1968. It takes into account mainly the heterogeneity of this movement, considering it as an area of dispute between different projects. Thus, in the context of the Civil-Military Dictatorship, students were split between support and resistance. The aim of this research is to express this diversity as from the city of Santa Maria and thereby questioning the generic assertions in the media and part of the historiography, that the Student Movement was homogeneously left-wing orientated or there would be a revolutionary essence among students. Based on interviews with activists, research in papers, minutes of the University Board, among other sources, is shown the performance of both opponents and supporters of the dictatorship. The study analyzes the electoral contests in the two major student organizations of the city, União Santamariense de Estudantes (USE) and the Diretório Central de Estudantes da Universidade Federal de Santa Maria (DCE-UFSM), and the action of organizations like the Grupo de Vanguarda Cultural and Movimento Decisão. This division, as it seeks to demonstrate this research, is quite noticeable in Santa Maria, however, is not restricted to the city. Attempts to articulate, both by the left-wing or the right-wing, indicate that disputes reached to the whole student movement in Rio Grande do Sul and in varying degrees, throughout Brazil. The time frame established in this work starts with the Coup of April 1, 1964, initiating the Civil-Military Dictatorship, and ends with the Institutional Act No. 5, on December 13, 1968, which modifies the dynamics of disputes between students.